A nonlinear optical active polymer film based on Pd(ii) dithione/dithiolate second-order NLO chromophores. Issue 43 (13th October 2016) - Espa, D.; Pilia, L.; Marchiò, L.; Artizzu, F.; Di Carlo, G.; Marinotto, D.; Serpe, A.; Tessore, F.; Deplano, P.
Abstract : A film of [Pd(Dod2 pipdt)(dmit)] incorporated into a polymethylmethacrylate matrix, showing a good second-harmonic generation, has been prepared for the first time in the class of dithione–dithiolate 2 nd order NLO-chromophores. Abstract : A film of [Pd(R2 pipdt)(dmit)] (1 ), where R2 pipdt = 1, 4-didodecyl-piperazine-2, 3-dithione (acceptor) and dmit = 2-thioxo-1, 3-dithiole-4, 5-dithiolate (donor) incorporated into a polymethylmethacrylate (PMMA) matrix, showing a good second-harmonic generation, has been prepared for the first time in the class of dithione–dithiolate 2nd order NLO-chromophores. Moreover full characterization of1, including molecular second-order NLO properties in solution, is reported.